2021
DOI: 10.3390/antiox10101632
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Cognitive and Affective Deficiencies Linked with Chronic Osteoarthritis Pain and Implicated Pathways by Slow-Releasing Hydrogen Sulfide Treatment

Abstract: Chronic osteoarthritis pain is accompanied by several comorbidities whose treatment has not been completely resolved. The anti-inflammatory, analgesic, and antidepressant effects of slow-releasing hydrogen sulfide (H2S) donors during osteoarthritic pain have been shown, but their actions in the accompanying memory impairment and anxious-like behaviors have not yet been demonstrated. Using female mice with chronic osteoarthritic pain, the effects of natural, diallyl disulfide (DADS) or synthetic, morpholin-4-iu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
3
12
0
Order By: Relevance
“…This work confirmed the memory deficits caused by PTX, as previously demonstrated by the reduced discrimination index in the novel object recognition test [14], and further proved that the administration of HRW normalized this cognitive impairment. These results are in accordance with the prevention of stress-induced decline of memory produced by the continuous consumption of HRW in mice [53], with the efficacy of other gases in inhibiting the memory deficits associated with chronic osteoarthritis pain [54] as well as with those produced by 7-chloro-4-(phenylselanyl) quinoline in animals with PIPN [55]. Several works indicated the contribution of the plasticity changes in memory impairments and that several drugs can improve these deficits by restoring the altered expression of MAPK activated by chemotherapy in the CNS [14].…”
Section: Discussionsupporting
confidence: 84%
“…This work confirmed the memory deficits caused by PTX, as previously demonstrated by the reduced discrimination index in the novel object recognition test [14], and further proved that the administration of HRW normalized this cognitive impairment. These results are in accordance with the prevention of stress-induced decline of memory produced by the continuous consumption of HRW in mice [53], with the efficacy of other gases in inhibiting the memory deficits associated with chronic osteoarthritis pain [54] as well as with those produced by 7-chloro-4-(phenylselanyl) quinoline in animals with PIPN [55]. Several works indicated the contribution of the plasticity changes in memory impairments and that several drugs can improve these deficits by restoring the altered expression of MAPK activated by chemotherapy in the CNS [14].…”
Section: Discussionsupporting
confidence: 84%
“…The blockage of the painkiller actions of HRW with the systemic and local injection of ML385, SnPP, and dicoumarol revealed the significant contribution of the central and peripheral antioxidant system in the painkilling effects of HRW during inflammatory pain. These outcomes were corroborated by other studies performed with H 2 [ 54 ] and with other compounds such as hydrogen sulfide donors and several antioxidants, which also activated the Nrf2/HO-1 and/or NQO1 pathway for alleviating chronic inflammatory, osteoarthritis, and neuropathic pain in rodents [ 5 , 21 , 45 , 55 ].…”
Section: Discussionsupporting
confidence: 74%
“…Other studies have further revealed that the injection of 4-HNE incites mechanical allodynia [ 43 ], and that an accumulation of 4-HNE may disrupt many cell signaling pathways, including the regulation of apoptosis [ 40 , 44 ]. Moreover, increased levels of 4-HNE and/or BAX have been detected in the AMG and PAG of nerve-injured animals, and in the AMG of animals with osteoarthritis pain [ 23 , 24 ]. In accordance with these data, we observed high levels of 4-HNE and BAX in the MS of sciatic nerve-injured mice, which were normalized with DADS and GYY4137 treatments, therefore revealing the antioxidant and antiapoptotic effects of both H 2 S donors in the MS of mice with nerve injury-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a gaseous neurotransmitter, widely distributed in the central (CNS) and peripheral (PNS) nervous systems, which modulates several physiological and pathological processes [ 21 , 22 ]. Recent preclinical studies have shown that treatment with two slow releasers of H 2 S, a component of garlic, diallyl disulfide (DADS), and a synthetic H 2 S donor, GYY4137 (morpholin-4-ium 4-methoxyphenyl(morpholino) phosphinodithioate dichloromethane complex), relieved neuropathic [ 23 ] and osteoarthritic pain [ 24 ]. The analgesic actions of both compounds were mainly produced by inhibiting apoptotic responses, and activating the endogenous antioxidant system by triggering the synthesis of antioxidant enzymes—such as superoxide dismutase 1 (SOD-1), glutathione S-transferase Mu 1 (GSTM1), heme oxygenase 1 (HO-1), and quinone oxidoreductase 1 (NQO1)—in the amygdala (AMG) and periaqueductal gray matter (PAG) of mice with nerve-injury-induced neuropathy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%